2018
DOI: 10.5182/jaie.29.140
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Fluoride Elution from Industrial Wastes with Portland Cement, Calcium and Magnesium Salts in Alkaline Region

Abstract: Recycling of fluoride industrial wastes is difficult to dispose, since the fluoride ions eluted again easily.In this study, newly effective inhibition method in both neutral and alkaline region for fluoride elution was investigated. Fluoride elution concentration from CaF 2 was 9.8 mg/L at pH 8.1 and 288.5 mg/L at pH 12.2 with water/solid ratio of 10. Additions of Ca(OH) 2 , CaCl 2 and NH 4 H 2 PO 4 could restrain fluoride elution concentration of CaF 2 to 0.22 mg/L in the neutral region. This inhibition of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, ettringite [Ca 6 Al 2 (SO 4 ) 3 (OH) 12 ·26H 2 O], which is formed during the hydration of ordinary Portland cement (OPC), showed a high removal preference for F [9][10][11], B [11][12][13][14][15], As [16,17], and Cr [12,[18][19][20][21] due to its ion exchange capacity by replacing SO 4 2− of ettringite. In our precious study, F concentration eluted from CaF 2 pure reagent could be reduced from 288.5 mg/L to 0.47 mg/L in alkaline regions with the addition of Ca(OH) 2 , MgCl 2 , and OPC [22]. The coprecipitation effect of Ca 2+ , ion exchange effect of ettringite, and solidification effect of Ca-bearing hydrates contribute to the decrease in the elution concentration of F. This has been successfully applied for the inhibition of F eluted from paper sludge and coal ash.…”
Section: Fluoride (F F − ) Boron (B [B(oh)mentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, ettringite [Ca 6 Al 2 (SO 4 ) 3 (OH) 12 ·26H 2 O], which is formed during the hydration of ordinary Portland cement (OPC), showed a high removal preference for F [9][10][11], B [11][12][13][14][15], As [16,17], and Cr [12,[18][19][20][21] due to its ion exchange capacity by replacing SO 4 2− of ettringite. In our precious study, F concentration eluted from CaF 2 pure reagent could be reduced from 288.5 mg/L to 0.47 mg/L in alkaline regions with the addition of Ca(OH) 2 , MgCl 2 , and OPC [22]. The coprecipitation effect of Ca 2+ , ion exchange effect of ettringite, and solidification effect of Ca-bearing hydrates contribute to the decrease in the elution concentration of F. This has been successfully applied for the inhibition of F eluted from paper sludge and coal ash.…”
Section: Fluoride (F F − ) Boron (B [B(oh)mentioning
confidence: 87%
“…Portlandite (Ca(OH) 2 [9] due to the high content of Ca 2+ , which originates from cement hydrates. Our previous studies have shown that the solubility of CaF 2 increases with an increase in pH in the alkaline range due to the competition between F − and OH − [22]. However, ettringite with a high ion exchange capacity was formed during the hydration of OPC, and therefore, the elution of F was inhibited due to the replacement of the exchangeable anion, such as SO 4 2− in ettringite by F. The coprecipitation effect of Ca 2+ , ion exchange effect of ettringite, and solidification effect of Ca-bearing hydrates contribute to the inhibition of the elution of F. Additionally, under the conditions of the same added amount of OPC, the elution concentrations of F were lower than those without additions of CSP.…”
Section: Suppression Of F Elutionmentioning
confidence: 99%